Preliminary study of alkaline pretreatment effect on carboxymethyl flour (CMF) from chiang mai university (CMU) purple rice properties - Anong Jainan (2018)
© 2017, Chiang Mai University. All rights reserved. “ Chaing Mai University (CMU)” purple rice is a variety generated from “Kao Kum“ black or purple rice. It has high anthocyanin content. This research aimed to synthesize carboxymethyl flour (CMF) characterization and properties, i.e., the degree of substitution (DS), physical properties, and chemical and thermal properties. Rice flour was treated with different alkaline concentrations; 10% to 40% (NaOH, w/v) in sequential reactions with monochloroacetate (MCA). The results revealed that NaOH concentrations had a significant effect on all of the CMF chemical properties. The optimal condition for achieving the highest anthocyanin content (7.66 mg/g of flour) and CMF content (88.7%) with 0.25 (DS) was found at 10% (w/v), NaOH. Tg, Tge1and Tmof CMF were approximately at 0.95-1.2°C 81.2-102.7 °C and 98.5-102.8 °C, respectively. Morphological properties were observed, and smoothness of the CMF granule surface lessened with increasing NaOH concentration.